2022
DOI: 10.3389/fmicb.2022.851706
|View full text |Cite
|
Sign up to set email alerts
|

Developing Multi-Copy Chromosomal Integration Strategies for Heterologous Biosynthesis of Caffeic Acid in Saccharomyces cerevisiae

Abstract: Caffeic acid, a plant-sourced phenolic compound, has a variety of biological activities, such as antioxidant and antimicrobial properties. The caffeic acid biosynthetic pathway was initially constructed in S. cerevisiae, using codon-optimized TAL (coTAL, encoding tyrosine ammonia lyase) from Rhodobacter capsulatus, coC3H (encoding p-coumaric acid 3-hydroxylase) and coCPR1 (encoding cytochrome P450 reductase 1) from Arabidopsis thaliana in 2 μ multi-copy plasmids to produce caffeic acid from glucose. Then, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The delta loci was often used for multicopy integration to enhance the expression of the target genes . After sequential optimization of the precursor l -tyrosine pathway for betanin biosynthesis, we proceeded to overexpress the OfCYP76AD8M10 , CcCYP76AD4 M465D , and MjCDGT genes at the delta loci of strain BEW7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delta loci was often used for multicopy integration to enhance the expression of the target genes . After sequential optimization of the precursor l -tyrosine pathway for betanin biosynthesis, we proceeded to overexpress the OfCYP76AD8M10 , CcCYP76AD4 M465D , and MjCDGT genes at the delta loci of strain BEW7.…”
Section: Resultsmentioning
confidence: 99%
“…The delta loci was often used for multicopy integration to enhance the expression of the target genes. 32 After sequential optimization of the precursor L-tyrosine pathway for betanin biosynthesis, we proceeded to overexpress the Of CY-P76AD8M10, CcCYP76AD4 M465D , and MjCDGT genes at the delta loci of strain BEW7. Forty-five clones were randomly selected for fermentation, and the highest titer of betanin was 56.9 mg/L with clone 26 (Figure 3D), which was designated as strain BEW8 with 68% higher than that of strain BEW7.…”
Section: Improvement Of Betanin Production By Engineeringmentioning
confidence: 99%
“…141 Recently, the multi-copy integration expression strategies based on delta sites were applied to integrate the genes of the CaA pathway into yeast and resulted in an increase of CaA production by 50 times compared to that produced by the initial multi-copy-plasmid expression. 142 Some other carbon sources and the whole-cell biocatalyst strategy have also been successfully used for CaA synthesis. 143,144 By introducing the xylose assimilation pathway into Candida glycerinogenes, the advantage of using mixed sugars as carbon sources showed that the optimized strain eventually obtained 1.2-fold higher CaA than that using glucose.…”
Section: Reviewmentioning
confidence: 99%